GANGGUAN BERBAHASA PADA PENYANDANG TUNAGRAHITA (STUDI ANALISIS PROSES PEMBELAJARAN BAHASA KELAS III SLB-C PERTIWI PONOROGO) - Setiawan, Agus; Nurwendah, Yusti Dwi; mahera, Intan anisaul (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2019)
This research reveals about language disorders which is type of disorders in communication with an indication of sufferers experiencing difficulties in the symbolization process. The language disorders referred to this study focused on people with mental disability (downsyndrome) in Ponorogo Extraordinary Schools at the elementary school level (three) as research subject. This study serves to reveal the types of language disorders experienced, the development and use of language, and the efforts or methods used by the teacher in the learning process. This research is qualitative research with a type of case study research. The techniques used in data collection include observation, interviews, and documentation. This research was conducted in 4 stages, pre-field, field work, data analysis, and research report writing. The results of the study show that in one class all of them are persons with different levels of resignation. The focused development is the development of cognitive, language, and social skills, using methods that are varied, according to the needs of each individual